Peranan Sila Ketuhanan dalam Mewujudkan Kesejahteraan Masyarakat - Ruth Yessika Siahaan; Yakobus Ndona (Jurnal Bintang Pendidikan Indonesia, 2024)
The role of Divine Principles in Pancasila is very significant in achieving the welfare of Indonesian society. As a moral and ethical foundation, Divine Principles encourage the formation of a harmonious and just society. This article discusses how the principle of belief in the Almighty God is the foundation for education, moral and ethical values, as well as the role of religious communities in everyday life. Through ontological, epistemological and axiological foundations, Divine Principles offer the view that humans have an inherent relationship with God, which emphasizes moral and spiritual responsibility in maintaining balance between humans, nature and His creator. This principle also encourages the development of character and attitudes that are in accordance with religious teachings, creating an environment full of love, tolerance and social justice. By integrating Pancasila values ​​in policies and regulations, Indonesia can build a prosperous and sustainable society. This article concludes that the Divine Principles of Pancasila are a solid foundation for achieving equitable and sustainable prosperity for all members of society.